ТАБЛИЦЫ КАК СПОСОБ ГРАФИЧЕСКОЙ ОРГАНИЗАЦИИ МАТЕРИАЛА - Ешниязова, Э.Н.; Турсынова, М.М. (SCIENCE and SOCIETY, 2022)
The article deals with the issues of graphic organization of the material, the use of support technologies in the learning process.
Keywords: supporting technologies; tables; diagrams; structure; creativity